Halal Food Industry Innovation in Jember (Study on Opportunities and Challenges) - Ach. Faqih Supandi; Istiadah Istiadah; Fais Faizul Hannan; Sigit Kusbiantoro (Mabsya, 2021)
Indonesia is a country that has great potential for the development of the halal industry. This is certainly one of the biggest opportunities in increasing the halal food industry with the influence of Indonesia's large Muslim population. Indonesia accounts for 12.7% of the world's Muslim population.